Spray Characteristic by using Phase Doppler Anemometry (PDA) and Laser Doppler Anemometry (LDV) - Mohd Akmal Bin Mohd Sobli, Mohd Akmal (Universiti Teknologi Petronas, 2008)
The main objective of this project is to study the existing of the on line size, velocity and concentration of droplets or bubbles suspended in bio ethanol and gasoline mixture. In this study, the test chamber has been fabricated to provide an optical access for laser penetration during spray injection process.